A contingência pandêmica e os impactos migratórios: uma análise dos atos normativos de fechamento da fronteira entre Brasil e Venezuela - Nicolli Bernardes Ribeiro (Institut des Amériques, 2021)
The year 2020 begins with the pandemic caused by the new coronavirus, bringing new dynamics that have become rules between countries: the closing of borders and the restriction of people's circulation. Such measures could be observed in different countries as the main alternatives for controlling the dissemination of the COVID-19 virus. The effects of the pandemic and the closing of borders, in the Brazilian case, demonstrated an aspect already known in the contexts of historical and contemporary migration in Brazil: migratory selectivity and the adoption of restrictive measures mediated by legal categories. Thus, a conjectural analysis of the first normative acts in Brazil will be presented, in dialogue with their specific treatment of Venezuelans, comparing them to each other, in order to observe the issues underlying the normative production of the related case.